Evaluation of the Effect of Type II Diabetes Mellitus on Bone Mineral Density of Upper and Lower Limbs by Dual-Energy X-Ray Absorptiometry - Abdel Aziz, Zainb A.; Dawood, Numan S.; Al-Khalisy, Maan H. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Bone mineral density has been assessed using Dual-Energy X-Ray Absorptiometry. Bone mineral density is measured according to the results of the Dual-Energy X-Ray Absorptiometry examination of the vertebral column and pelvis. Although diabetes mellitus type II (DM) is known to affect bone mineral density, at the present time this particular relationship is not clear. Objective: The aim of the current study was to evaluate the effects of type II diabetes mellitus on bone mineral density of the upper and lower limbs as well as gender differences. Methods: This study involved 165 patients complaining of bone pain (85 males and 80 females), and 85 patients who suffered from diabetes, involving both genders. In addition, 90 apparently healthy volunteers had been studied and were considered to constitute the control group. All individuals (255) were studied regarding their bone mineral density via Dual-Energy X-Ray Absorptiometry for all parts of the body. Results: The Dual-Energy X-Ray Absorptiometry exam revealed highly statistically significant differences between the sides of the body in the same person. In addition, there were significant differences in bone mineral density between females and males, as well as between the control and patient groups with type II diabetes mellitus. Conclusion: Our results indicated that the bone mineral density of women was less than that in men in all cases (normal, osteoporosis, and diabetes mellitus type II (DM) with osteoporosis). Other results obtained from this research revealed that diabetes mellitus type II (DM) can be considered to be one of the major causes of osteoporosis in the general population